2008
DOI: 10.1128/jcm.00719-08
|View full text |Cite
|
Sign up to set email alerts
|

Association between 16S-23S Internal Transcribed Spacer Sequence Groups of Mycobacterium avium Complex and Pulmonary Disease

Abstract: Organisms within the Mycobacterium avium complex (MAC) may have differential virulence. We compared 33 subjects with MAC pulmonary disease to 75 subjects with a single positive culture without disease. M. avium isolates were significantly more likely to be associated with MAC pulmonary disease (odds ratio ‫؍‬ 5.14, 95% confidence interval ‫؍‬ 1.25 to 22.73) than M. intracellulare.Exposure to aerosols containing organisms in the Mycobacterium avium complex (MAC) likely occurs often (11, 12), but resultant pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…No consensus definition of copy numbers has been agreed upon for nontuberculous mycobacteria. The majority of VNTR types had the Mav-B and Mav-A ITS sequences (which differ by a single base pair), which has been noted in other studies (1,24,28). For multiple isolates of the same VNTR type from the same patient, only one was sequenced; the results for the rest were presumed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No consensus definition of copy numbers has been agreed upon for nontuberculous mycobacteria. The majority of VNTR types had the Mav-B and Mav-A ITS sequences (which differ by a single base pair), which has been noted in other studies (1,24,28). For multiple isolates of the same VNTR type from the same patient, only one was sequenced; the results for the rest were presumed.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis revealed that 33 types or subtypes were Mav-B (58.9%), 18 were Mav-A (32.1%), 3 were Mav-F (5.4%), 1 was Mav-G (1.8%), and 1 did not amplify. Other previously described ITS sequences in isolates of M. avium (Mav C, Mav-D, and Mav-E sequences) were not encountered (1,24,28). Of the three reference strains of M. avium subsp.…”
Section: Pfgementioning
confidence: 99%
See 2 more Smart Citations
“…Variable-number tandem (i.e., consecutive) repeats (VNTR) of the minisatellite class (10 to 100 bp) were identified. VNTR typing has been used for strain comparison and population studies of other species of mycobacteria, including Mycobacterium ulcerans, Mycobacterium avium, and Mycobacterium tuberculosis (8)(9)(10)(11)(12)(13)(14)(15). Subsequently, studies of the use of VNTR for M. intracellulare isolates were reported in 2009 and 2010 from Japan (16) and (Bordeaux) France (17), and the candidate markers were described as mycobacterial interspersed repetitive unit-variable-number tandem repeats (MIRU-VNTR) (17).…”
mentioning
confidence: 99%